1991
DOI: 10.1002/pros.2990180303
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in plasminogen activator (PA) levels in human prostate cancer cell lines: Increased PA activity correlates with biologically aggressive behavior

Abstract: Plasminogen activators (PA), particularly the lower Mr urokinase (u-PA) type, have been associated with tumor cell invasion and metastasis. We have examined the expression of PA by two human prostate cancer cell lines (PC-3 and DU-145) using functional and immunologic techniques. The culture media and cell extracts of the more aggressive PC-3 cell line contained more than two-fold greater PA activity than the relatively indolent DU-145 cell line. Zymographic studies identified the PA expressed as u-PA. PC-3 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 18 publications
2
34
0
Order By: Relevance
“…In contrast, Laniado et al (57) showed a narrow range of variation between these two prostate cancer cell lines, whereas Dahiya et al (58) reported a higher invasive capacity for LNCaP cells. Keer et al (59) reported that PC-3 cells had a considerably higher invasive capacity compared with DU-145 cells in agreement with the present study. Explanations for these differences include, variations within cell lines and/or the loss of certain adhesion molecules over time and passage number and also differences in the expression of MMP activity as shown in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, Laniado et al (57) showed a narrow range of variation between these two prostate cancer cell lines, whereas Dahiya et al (58) reported a higher invasive capacity for LNCaP cells. Keer et al (59) reported that PC-3 cells had a considerably higher invasive capacity compared with DU-145 cells in agreement with the present study. Explanations for these differences include, variations within cell lines and/or the loss of certain adhesion molecules over time and passage number and also differences in the expression of MMP activity as shown in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…studies have shown that PC3 cells are highly metastatic, whereas DU145 and LNCaP cells are moderately and poorly metastatic, respectively (45)(46)(47)(48). Because uPA and its receptor uPAR are involved in tumor invasion and metastasis, we first compared the levels of these proteins in the three human prostate cancer cell lines with different metastatic potentials.…”
Section: Endogenous Upa and Upar Protein Expression Is Associated Witmentioning
confidence: 99%
“…4A). In PC3 cells, which have a high metastatic potential (20,27), pioglitazone treatment showed no significant effect on invasiveness of the cells compared to that of the control vehicle-treated cells (41.9% Ϯ 2.0% for control-treated cells versus 32.2% Ϯ 8.6% for pioglitazone-treated cells), whereas decreased invasion was observed when PC3 cells were treated with valproic acid (24.0% Ϯ 2.3%). Strikingly, a synergistic effect on the inhibition of invasion was observed when a combination of pioglitazone and valproic acid was used (11.4% Ϯ 3.1%).…”
Section: Synergistic Action Of Ppar␥ Agonists and Hdac Inhibitorsmentioning
confidence: 91%